2010
DOI: 10.1111/j.1526-4610.2009.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

HIT‐6 and MIDAS as Measures of Headache Disability in a Headache Referral Population

Abstract: The HIT-6 and MIDAS appear to measure headache-related disability in a similar fashion. However, some important differences may exist. Headache intensity appears to influence HIT-6 score more than the MIDAS, whereas the MIDAS was influenced more by headache frequency. Using the HIT-6 and MIDAS together may give a more accurate assessment of a patient's headache-related disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 33 publications
7
103
0
2
Order By: Relevance
“…While it is important clinically to know the number of headache days, such a value only provides headache day frequency, but it does not reflect to what extent headache affects the sufferer’s daily life. Our findings regarding the relative strength of the association between HIT-6 scores and headache pain intensity and headache frequency agree with those of another study (40) that also reported HIT-6 scores to be more strongly associated with headache pain severity than with headache frequency. However, in another study (41) headache frequency, but not headache severity, was strongly related to HIT-6 scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While it is important clinically to know the number of headache days, such a value only provides headache day frequency, but it does not reflect to what extent headache affects the sufferer’s daily life. Our findings regarding the relative strength of the association between HIT-6 scores and headache pain intensity and headache frequency agree with those of another study (40) that also reported HIT-6 scores to be more strongly associated with headache pain severity than with headache frequency. However, in another study (41) headache frequency, but not headache severity, was strongly related to HIT-6 scores.…”
Section: Discussionsupporting
confidence: 92%
“…However, in another study (41) headache frequency, but not headache severity, was strongly related to HIT-6 scores. In this latter study, pain severity was measured through headache diaries, whereas our study and the study of Sauro (40) assessed pain severity through a single question. This important methodological difference may account for the disparity in findings.…”
Section: Discussionmentioning
confidence: 99%
“…Using the HIT-6 and MIDAS together was advocated to give a more accurate assessment of a patient’s headache-related disability. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[34, 54] The HIT-6 consists of six items (pain, social functioning, role functioning, vitality, cognitive functioning, psychological distress) where respondents select one of five options: “never,” 6 points; “rarely,” 8 points; “sometimes,” 10 points; “very often,” 11 points; “always,” 13 points. Total score ranges from 36 to 78 points.…”
Section: Methodsmentioning
confidence: 99%